Food Vlogger vs. e-WoM: Preferensi Kepercayaan Konsumen dalam Memilih Tempat Makan di Pekanbaru - Johan Faladhin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study examines consumer trust preferences in Pekanbaru when choosing dining places, comparing the influence of reviews from food vloggers and electronic Word of Mouth (e-WoM). The study employs Consumer Behavior Theory as the theoretical framework and a descriptive qualitative approach to analyze data obtained from interviews with 20 informants. The results show that consumer trust preferences are influenced by a combination of both sources of information. Most consumers use food vlogger reviews to get an initial impression and then verify this information by reading e-WoM from other consumers. This research has implications for culinary MSMEs in Pekanbaru to utilize food vlogger reviews and e-WoM as effective marketing strategies. Transparency, honesty, and consistency in reviews are key factors in building consumer trust. Social interactions on social media significantly influence consumer purchasing decisions, especially in the culinary MSME sector. Therefore, MSMEs need to leverage these interactions to build and maintain consumer trust through word of mouth.